Atmospheric dry and wet deposition of sulphur and nitrogen species and assessment of critical loads of acidic deposition exceedance in South Africa - Miroslav Josipovic; Harold Annegarn; Melanie Kneen; Jacobus Pienaar; Stuart Piketh (South African Journal of Science)
We tested the hypothesis that acidic atmospheric pollution deposition, originating from the South African central industrial area, poses an environmental threat across a larger region within the dispersal footprint. A network of 37 passive monitoring sites to measure SO2 and NO2 was operated from August 2005 to September 2007. The area extended over the entire northern and eastern interior of South Africa. Monitoring locations were chosen to avoid direct impacts from local sources such as towns, mines and highways. Dry deposition rates of SO2 and NO2 were calculated from the measured concentrations. Concentrations of sulphur and nitrogen species in wet deposition from a previous study were used in conjunction with measured rainfall for the years 2006 and 2007 to estimate the wet deposition over the region. The calculated total (non-organic) acidic deposition formed the basis for an assessment of exceedance of critical loads based on sensitivity of the regional soils. Regional soil sensitivity was determined by combining two major soil attributes available in the World Inventory of Soil Emission Potentials (International Soil Reference and Information Centre). Results indicate that certain parts of the central pollution source area on the South African Highveld have the potential for critical load exceedance, while limited areas downwind show lower levels of exceedance. Areas upwind and remote areas up and downwind, including forested areas of the Drakensberg escarpment, do not show any exceedance of the critical loads.